White popinac as potential phyto-coagulant to reduce turbidity of river water. - Mamun, Abdullah Al; Basir, Ahmad Tsaqif A (Asian Research Publishing Network (ARPN), 2016)
One of the main problems in many rivers is high turbidity. People lose attraction to rivers if the water is turbid. Reduction of turbidity is also one of the main objectives to achieve acceptable water quality for municipal water supply. Turbidity is generally removed by adding chemical coagulants, which show good result, but less environment friendly. Therefore, a significant amount of research is needed to discover efficient biodegradable coagulant to reduce turbidity of water. This study investigated the potential use of phyto-coagulants for turbidity reduction in synthetic and river water. Among the four phyto-ingredients tested, white popinac was found to be efficient in reducing the turbidity of river water by 76% at 50 mg/L with initial turbidity of 319 NTU. The efficiency of white popinac in reducing synthetic turbid water was not as profuse as seen in river water. Thus, white popinac being a non-toxic element and posing no threat to human health could be used as a potential coagulant to reduce turbidity of water. However, further experimentations are needed to ascertain the toxicological and antiseptic aspects of white popinac for wider applications, which is reported to be consumed occasionally by local people for several health benefits.